Pakaian Tradisional Laki-Laki Teluk Arab sebagai Identitas Budaya melalui Novel Nāqatu Ṣāliḥah Karya Sa‘ūd As-San‘ūsī - Azizah, Annisa Nurul (Middle Eastern Studies Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
This research aims to reveal the types of traditional Arabian Gulf men's clothing in the novel Nāqatu Ṣāliḥah by Sa'ūd as-San'ūsīand its function in shaping the Arabian Gulf’s cultural identity, also to reveal the construction of the Arabian Gulf’s cultural identity through the current clothing practices of the community. This research utilizsa qualitative research method and was conducted through three steps, there are; data collecting, data analysis, and presentation of data analysis results. The results of this study found that, there are four types of traditional Arabian Gulf men's clothing in the novel Nāqatu Ṣāliḥah, there are gutrah, ‘iqāl, thobe, and Najdi sandals. These four types of clothing isnot only functioned as body’s protection, but also play an important role in the formation of cultural identity for daily lives of male characters in the novel and serve as a language of representation to construct the Arabian Gulf’s cultural identity. The wearing of traditional clothing and its style of clothing can indicate the people’s regional origin and even their mood. Currently, the practice of wearing traditional clothing plays an important role in constructing the Arabian Gulf’s cultural identity amid the influx of foreign workers into the region. The wearing of traditional clothing serves to strengthen national pride, preserve ancestral cultural heritage, and reinforce the Arabian Gulf’s cultural identity. This practice of wearing traditional clothing is also supported by mandatory rules regarding traditional attire during working hours and official events for government employees, as established by the governments of Saudi Arabia and Qatar. The practice of wearing traditional clothing also plays a role in preserving the cultural identity of the Arabian Gulf amid the tide of globalization and modernization, as well as distinguishing the Arabian Gulf’s cultural identity from other societies. Overall, traditional male attire can serve as a language of representation to construct the Arabian Gulf’s cultural identity.